The utility of post-conviction polygraph testing among sexual offenders - Elliott, Elizabeth; Völlm, Birgit (SAGE, 2016)
It is often difficult to ascertain the true extent and nature of sexually deviant behavior, as much relies on self-report or historic information. The polygraph has been proposed as a useful tool in the treatment and supervision of sex offenders. The current review aims to provide a coherent, objective, and recent synthesis of evaluation studies exploring the utility of the post-conviction polygraph (PCSOT) in the treatment and management of sexual offenders. This was assessed based on offense recidivism rates and disclosure; self-reported utility was also considered. Nineteen studies were identified from the United States, the United Kingdom, and the Netherlands with no randomized controlled trials identified. Overall, there was a significant increase in relevant disclosures associated with the polygraph. The impact on reoffending rates was significant for violent but not sexual offenses. A number of methodological factors introduced the potential for bias in a significant number of studies reviewed in this review.